Cr/Sc multilayer radiator for parametric EUV radiation in "water-window" spectral range - Uglov S. R. Sergey Romanovich; Kaplin V. V. Valery Viktorovich; Kubankin A. S.; Andre J. M.; Guen K. Le.; Jonnard Ph.; Rossi S de.; Meltchakov E.; Delmotte F. (Parametric X-Radiation, 2016)
Title screen